Nanoparticle‐Assisted Affinity NMR Spectroscopy: High Sensitivity Detection and Identification of Organic Molecules. Issue 47 (10th October 2016) - Diez‐Castellnou, Marta; Salvia, Marie‐Virginie; Springhetti, Sara; Rastrelli, Federico; Mancin, Fabrizio
Abstract: A simple and effective method for high‐sensitivity NMR detection of selected compounds is reported. The method combines 1D NMR diffusion filter experiments and small monolayer‐protected nanoparticles as high‐affinity receptors. Once bound to the nanoparticles, the diffusion coefficient of the analyte decreases in such way that spectral editing based on diffusion filters can separate its signals from those of other mixture components. Using nanoparticles functionalized with Zn 2+ ‐triazacyclonane complexes, detection and identification of phosphorylated organic molecules can be achieved. Diphenyl phosphate can be detected at 25 micromolar concentration with good selectivity. The selectivity toward organic carboxylates is enhanced at pD=3.75. In these conditions, commercial tablets containing betamethasone phosphate and a large excess of benzoate could be successfully analyzed. Abstract : Diffusion‐filtered NMR spectroscopy in combination with high affinity nanoparticle‐based receptors allows for the detection of phosphorylated organic molecules with remarkable sensitivity. The method combines 1D NMR diffusion filter experiments and small monolayer‐protected nanoparticles as high affinity receptors.